Letter to Jane Tolmach from May Layne Bonnell - May Layne Bonnell:::::: (1961)
A letter to Jane Tolmach from May Layne Bonnell thanking her for her letters on behalf of the Ventura County Democratic Central Committee that recommending two people to the Board of Trustees of Camarillo State Hospital.